Frequency and Severity of Vitamin D Deficiency among Vitiligo Patients - Shifa Bibi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Vitiligo is a chronic depigmenting disorder of the skin, often associated with autoimmune diseases. Vitamin D, a crucial fat-soluble vitamin, plays a key role in immune modulation and skin health. The relationship between vitamin D deficiency and vitiligo has been a subject of various studies, but the frequency and severity remain under-researched. This study aims to assess the prevalence of vitamin D deficiency in vitiligo patients and investigate any correlation between deficiency levels and vitiligo severity. Methods: This cross-sectional study was conducted at Department of Dermatology Khyber Teaching Hospital Peshawar from July 2022 to Dec 2022. Total 105 vitiligo patients who were examined for their serum 25-hydroxyvitamin D (25(OH)D) levels were included. The severity of vitiligo was measured using the Vitiligo Area Scoring Index (VASI). Logistic regression was used to identify factors influencing vitamin D deficiency. Results: The study found that 68% of the patients were vitamin D deficient, with the deficiency more pronounced in those with generalized vitiligo compared to segmental vitiligo. A significant negative correlation was observed between the severity of vitiligo (VASI score) and serum vitamin D levels. Logistic regression analysis revealed that generalized vitiligo and older age were significant predictors of vitamin D deficiency. Conclusion: Vitamin D deficiency is highly prevalent among vitiligo patients, particularly those with generalized vitiligo. The findings suggest the importance of monitoring and managing vitamin D levels in vitiligo patients, as it may play a role in the pathogenesis and progression of the disease. Keywords: Vitamin D deficiency, Vitiligo, 25-hydroxyvitamin D, VASI score, Autoimmune diseases, Serum levels.